Carbon supported heterostructured Pd–Ag nanoparticle: Highly active electrocatalyst for ethylene glycol oxidation. (9th February 2015) - Yang, Yan; Wang, Wei; Liu, Yanqin; Wang, Fengxia; Zhang, Zhe; Lei, Ziqiang
Abstract In this study, a carbon supported heterostructured Pd–Ag (Pd–Ag/C) catalyst is fabricated. Supported nanoparticle has an obvious adjacent interface between Ag and Pd in the Pd–Ag/C catalyst, which leads to the enhanced electrocatalytic performance of Pd for the ethylene glycol oxidation. Compared to monometallic Pd/C catalyst, the onset potential of Pd–Ag/C catalyst is negative 0.25 V and the jf/jb of Pd–Ag/C is larger. Notablely, the current of Pd–Ag/C catalyst is about 4.85 times than that of Pd/C catalyst. Additionally, the stability of the Pd–Ag/C is also superior to the Pd/C. These make Pd–Ag/C catalyst promising in large-scale practical application.